Stress at Work, Gendered Dys‐appearance and the Broken Body in Policing. Issue 1 (2nd April 2017) - Yates, Sarah; Riach, Kathleen; Johansson, Marjana
Abstract : This paper explores how stress as a gendered mode of perception is characterized by processes that call the body to attention in ambiguous and incomplete ways — an experience Leder terms 'bodily dys‐appearance'. Extending Leder's work through an engagement with feminist accounts of embodiment, we show how stress, as constituted through a corporeal demand to pay attention to pain or discomfort, becomes negated or misrecognized through the sociocultural, organizational or occupational privileging of normative masculinity. Our analysis of 20 in‐depth interviews with female police managers in England explores the dys‐appearance of stress in the context of policing, and the professional and bodily consequences of negotiating stress as a gendered mode of perception. This suggests the compulsion to make sense of bodily sensations cannot be separated from the systems, structures and ways of understanding that privilege masculinized knowledge claims. Questioning these claims may allow for a plurality of stress experiences to be recognized beyond patriarchal ways of organizing, and give voice to other body episodes that elude articulation or representation within normative organizational practices.